고유변동성 이상 현상의 강건성에 관한 검토 - 옥영경(Youngkyung Ok); 안승철(Seungcheol An); 김정무(Jungmu Kim) (한국증권학회지, 2018)
본 연구는 한국 주식시장에서 보고된 고유변동성 이상 현상의 강건성을 검토한다. 기존 국내외 연구에서이용된 방법론상의 공통된 큰 틀을 유지하되, 세부적인 연구 설계에 6가지 차이를 두어 결과를 비교한다. 방법론상의 큰 틀로서, 고유변동성을 기준으로 정렬한 5분위 포트폴리오의 양극단을 매수-매도하는방식으로 헤지 포트폴리오를 구성한 후 평균수익률의 크기와 유의성을 살펴본다. 이때, 세부적인 연구설계에 있어, 1) 체계적 위험의 정의, 2) 변동성 추정 기간, 3) 포트폴리오 정렬 분기점, 4) 수익률 가중방식, 5) 분석기간, 6) 표본구성에 각각 변화를 두어 헤지 포트폴리오 수익률의 크기와 유의성이 영향을받는지 검토하였다. 체계적 위험의 정의는 이상 수익률 유의성에 영향을 미치지 않았으며, 이를 제외한각 연구 설계 조건은 이상 수익률의 유의성에 영향을 주었다. 구체적으로, 고유변동성 이상 현상은, i) 과거 3～12개월의 장기 데이터를 이용하여 고유변동성을 추정하고, ii) 포트폴리오를 단순 정렬하여, iii) 가치가중 방식으로 수익률을 계산한 경우에만 강건성을 유지하였다. 특히, 이상 수익률의 강건성을가장 크게 약화시키는 연구 설계는 포트폴리오 정렬 분기점인 것으로 나타났다. 동일 시장가치 비중을가지도록 포트폴리오를 구성하면, 유의한 이상 수익률을 관측하는 조건을 찾아내기 힘들었다. 따라서본 연구의 결과는 선행연구들의 주장과는 달리 한국시장에서의 고유변동성 이상 현상은 강건하지않음을 보여준다. The study examines if idiosyncratic volatility (IVOL) puzzle reported in the Korean stock market is robust. While employing a common framework shared in the literature, we investigate how specific research design affects the robustness of the results. Specifically, we examine if the magnitude and statistical significance of average returns on long-short portfolios on a basis of idiosyncratic volatility are robust to different research designs: 1) definition of systematic risk, 2) period of estimation of volatility, 3) breakpoints, 4) weighting scheme, 5) sample period, 6) sample composition. We find that the research design affects the anomaly, except the definition of systematic risk. More specifically, the IVOL anomaly is robust only to the case where we use i) 3～12 month periods for the IVOL estimation, ii) KSE breakpoint for sorting, iii) value-weighting scheme for the portfolio return computation. In particular, breakpoint weakens the robustness the most. Constructing portfolios with equal market shares, we fail to find any condition under which abnormal return on the long-short portfolio is statistically significant. Contrary to previous studies, we argue that the IVOL puzzle is not robust in the Korean stock market. KCI Citation Count: 3